Whole-mount in situ hybridization of small invertebrate embryos using laboratory mini-columns. (December 2007) - Irvine, Steven Q.
To facilitate the handling of small invertebrate embryos during whole-mount in situ hybridization, a method of solution exchange using laboratory mini-columns was developed. This protocol speeds time-consuming aspiration of buffers, and avoids accidental loss of the embryos, by gently pushing solutions through the column using air pressure from a syringe after each incubation. The next buffer is then added using a pipettor. Embryos are retained on a filter within the column. As many columns as desired may be processed in parallel for different probes or stages.